Cost analysis of innovative biomass harvesting systems for young dense thinnings - Bergström, Dan (Array, 2019)
The objective was to analyze three innovative harvesting systems for early thinnings and compare forest-to-industry supply costs. FlowConv consists of a harvester equipped with an innovative continuously cutting, accumulating and bunching head (the FlowCut head), a forwarder and a truck to transport loose tree-parts. FlowFix consists of a harvester equipped with the same cutting head but also a bundling unit (the Fixteri system), plus a forwarder and roundwood truck for biomass transport. FlowCin consists of a new conceptual biomass harvester (the Cintoc system) equipped with the same cutting head and a second crane to pass the cut trees from the front of the machine to a bundling unit at the back, plus the same forwarding and trucking units as in the FlowFix system. Empirical data were used to assess the FlowConv system’s performance, while the FlowFix and FlowCin systems’ performance was simulated. Results indicate that supply costs of the FlowCin system would be 6–10% and 24–29% lower than those of the FlowFix and FlowConv systems, respectively. Thus, it would be more suitable to be equipped with an innovative cutting head, which is up to 100% more efficient than the current commercially available options. Key features of the Cintoc-based system (which minimize possible waiting times during operation) include its buffering cradle and delivery of biomass acquired in two cutting crane cycles to the intermediate delivering crane. The apparent superiority of the FlowCin system is consistent with previous conclusions regarding developments needed to maximize the cost-effectiveness of harvesting young dense stands.